From Mindset to Management: How Psychological Capital Shapes Student Leaders’ Managerial Functions - Alnico Imam Nugroho (Universitas Negeri Surabaya, 2025)
This study investigates the predictive role of psychological capital self-efficacy, hope, optimism, and resilience on the implementation of managerial functions (POAC) among student leaders in higher education. Using a quantitative approach with multiple regression analysis, data were processed through Jamovi 2.3.6 following descriptive, assumption, and correlational testing. Results indicate that psychological capital strongly predicts POAC implementation, with the regression model explaining 71.9% of the variance (R = .848; R² = .719; p < .001). All four dimensions significantly contributed to managerial performance, with self-efficacy emerging as the strongest predictor, followed by hope, optimism, and resilience. These findings highlight psychological capital as a central psychological resource that enhances planning, organizing, actuating, and controlling behaviors in student organizational contexts. The study underscores the importance of integrating psychological capital development into leadership training initiatives to strengthen managerial readiness and organizational effectiveness in university based leadership environments.